Spiritual Anthropology: Man and His Spiritual Position in Rumi’s Doctrine - Ahmad, Baharudin (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2012)
Fritjof Schuon (2002) in one of his works suggested the need for a ‘spiritual anthropology’ to re-identify the meaning of man1. In modern anthropology man is simply a creature that exists in the natural world with the tendency to survive and to improve his self in accordance with the changing conditions of his natural and social environment. In different branches of modern knowledge, such as anthropology, sociology and psychology the image of man is no more than a natural creature that creates his living conditions by adaptation and improvement as allowed by the natural and social conditions surrounding him. It is in the works of Mawlana Jalaluddin Rumi and Sufist in general, as well as other metaphysicians of the Oriental traditions, that one can find the abundant discussions on the concept of man, his reality, both spiritual and bodily as well as his potential force that is inherent within him to transcend his limited elemental or bodily self and able to realize his inner self that portrays him as he really was in the very beginning. This paper will discuss the above need to understand the meaning of man by using the arguments of the great thinker, Mawlana Rumi in his works especially the Divan Shams al-Tabriz, and relates his concepts to re-identify the meaning and the inner dimension of man in religious teachings.